Production of Alkaline Lipase from Kluyvera KB4 - Retno Indrati; V.S. Pertiwi Rumiyati; Tyas Utami (Indonesian Food and Nutrition Progress, 1998)
Kluyvera KB4 produced alkaline lipase in a medium containing oil as inducer. Optimum conditions for lipase production were determined in terms of composition of medium, pH, temperature and time of incubation. The highest lipase productivity was obtained from a medium with corn oil as carbon source and peptone as nitrogen source. Oils seem to be. an essential carbon source, since in a medium containing sorbitol without addition of oil the lipase production was very low, approximately only 14%. However, higher concentration of oil (2%) suppressed the lipase production. Production of lipase was greatly influenced by pH of the medium and incubation temperature. It was optimally active at pH 7.5 and 37 Â°C in medium containing peptone and corn oil 1 %, respectively. Under optimum condition (pH 7.5, at 37 Â°C), the highest lipase activity was obtained after 36 h of incubation.